Pre- and in-season strength and conditioning training changes in leg peak power performance in collegiate Division II women`s basketball team: A case study - Anderson, A. B.; Key, C. M.; Sanders, B. K.; Papadakis, Z. (International Journal of Exercise Science Conference Proceedings, 2019)
Basketball is a team sport that places emphasis on explosive movements. Leg peak power (PP) performance provides an advantage for successful basketball participation. Pre-season (PS) strength and conditioning training (SCT) sets the foundation for in-season (IS) success. However, determining the optimal duration, of PS and IS SCT to develop improvements in PP is still under investigation. PURPOSE: To describe the changes over time in PP during a 4 weeks of PS and 6 weeks of IS SCT in a collegiate Division II women`s basketball team. METHODS: Besides PS in-court sessions (4.5 hrs/wk), 14 female players completed 3 hrs/wk of SCT. During the IS, the in-court sessions increased (10 hrs/wk), while the SCT reduced to 2 hrs/wk, focusing on strength (weeks 5-8), then on strength and power (weeks 9 and 10). All SCT sessions were supervised by SCT coach. PP was assessed 1 d/wk for 10 weeks by the counter-movement jump (CMJ) test performed on the Just Jump© mat. PP was calculated based on Sayers formula. PP data were normalized for body size using allometric scaling, from recorded PP scores and body mass (M) (PPn=PP/M0.67). PP scores were analyzed using one-way repeated measures ANOVA. Missing values were replaced with series mean. Statistical significance was set at p = 0.05. All statistical analyses were performed using SPSS© (vs.25). RESULTS: Mauchly`s test indicated that assumption of sphericity has been violated, x2 (44) = 96.58, p = 0.000, therefore Greehouse-Geisser corrected tests are reported (e = 0.41). PP scores were significantly different between the 10 weeks of SCT, F (3.65, 47.40) = 4.80, p = 0.003, 2 = 0.270. Post hoc test using the Bonferroni correction revealed that SCT increased PP scores at week-3 compared to week-1 and week-2, but that increase was not significant (225.03 ± 16.50 W · kg-0.67 vs 212.90 ± 17.01 W · kg-0.67, p = 0.69 and 214.01 ± 19.13 W · kg-0.67, p = 0.41). PP scores for week-7 (209.19 ± 13.5 W · kg-0.67) were significantly different than week-3 and week-4, and week-5 (225.03 ± 16.50 W · kg-0.67, p = 0.01; 219.69 ± 13.33 W · kg-0.67,p = 0.02; 218.12 ± 12.98 W · kg-0.67, p = 0.01). Following week-7, PP scores increased but not significantly at week-8 and week-9 (211.46 ± 12.30 W · kg-0.67, p = 1.00; 214.24 ± 15.18 W · kg-0.67, p = 0.67) and then at week-10 (212.36 ± 10.78 W · kg-0.67, p = 1.00) PP scores non-significantly decreased below to week-1 scores. CONCLUSION: SCT on PP performance in women`s collegiate DII basketball athletes during PS and IS are subjected to the time devoted on SCT itself. Three hrs/wk for 3 weeks seems to be adequate stimulus to elicit an increase PP. Continuing a SCT program for more than 3 weeks with less than 3 hrs/wk is not enough to maintain the already achieved adaptations. More than 7 weeks and up to 10 weeks of SCT with 2 hrs/wk has no influence on improving PP above baseline week one values. Time constraint is at expense of SCT. For SCT and basketball coaches, this study may be a useful tool when developing a periodized SCT program focusing on strength and power adaptations.